Crew Route Scheduling Using the Multiple Traveling Salesman Problems - Amartei, Percy Nii Amaa (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science, 2011